Assessing berry number for grapevine yield estimation by image analysis: case study with the white variety “Arinto” - Genuardi, Sergio (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto